(untitled) (Computer Aided Drug Development, 2024)
Author Dr. Bala Venkata Sivaram Nallamolu Professor and HOD, Dept. of Pharmaceutics, Sir C R Reddy College of Pharmaceutical Sciences, Eluru, Andhra Pradesh, India Abstract Computational tools and digital analysis systems have transformed the development of pharmaceutical emulsions and microemulsion drug carriers. These modern approaches integrate molecular modeling, statistical analysis, and artificial intelligence to predict and optimize critical formulation parameters. Through sophisticated algorithms and simulation techniques, formulators can efficiently analyze surfactant-oil-water interactions, predict phase behavior, and assess stability characteristics. The implementation of computer-aided design in emulsion development enables precise prediction of particle size distribution, interfacial phenomena, and long-term stability. These systems facilitate rational selection of surfactant combinations and co-surfactants while minimizing experimental burden. Advanced computational methods also support the development of microemulsion systems through automated analysis of phase diagrams and optimization of surfactant ratios. Quality by Design principles, integrated with computational approaches, ensure systematic development of stable emulsion systems. These tools enable efficient exploration of formulation space, prediction of system behavior, and optimization of drug loading capacity. Keywords: Emulsion formulation; Microemulsion systems; Computer-aided design; Phase behavior prediction; Surfactant optimization; Molecular modeling View PDF